14th of April Fund : inter-departmental correspondence (copy) - Tewson, Vincent
034-0018-001 H.V. TEWSON Secretary's Mr. G. STOLZ 12th June, 1942. 14th of APRIL FUND Will you be good enough to ask Mr. Carrillo to write to me telling me what he knows about the above Fund, so that I can send it to our correspondents? 292/946/34/18